Senescence in Primary Rat Astrocytes Induces Loss of the Mitochondrial Membrane Potential and Alters Mitochondrial Dynamics in Cortical Neurons - Morales-Rosales, Sandra Lizbeth; Santín-Márquez, Roberto; Posadas-Rodriguez, Pedro; Rincon-Heredia, Ruth; Montiel, Teresa; Librado-Osorio, Raúl; Luna-López, Armando; Rivero-Segura, Nadia Alejandra; Torres, Claudio; Cano-Martínez, Agustina; Silva-Palacios, Alejandro; Cortés-Hernández, Paulina; et al. (Frontiers in Aging Neuroscience, 2021)
The decline in brain function during aging is one of the most critical health problems nowadays. Although senescent astrocytes have been found in old-age brains and neurodegenerative diseases, their impact on the function of other cerebral cell types is unknown. The aim of this study was to evaluate the effect of senescent astrocytes on the mitochondrial function of a neuron. In order to evaluate neuronal susceptibility to a long and constant senescence-associated secretory phenotype (SASP) exposure, we developed a model by using cellular cocultures in transwell plates. Rat primary cortical astrocytes were seeded in transwell inserts and induced to premature senescence with hydrogen peroxide [stress-induced premature senescence (SIPS)]. Independently, primary rat cortical neurons were seeded at the bottom of transwells. After neuronal 6 days in vitro (DIV), the inserts with SIPS-astrocytes were placed in the chamber and cocultured with neurons for 6 more days. The neuronal viability, the redox state [reduced glutathione/oxidized glutathione (GSH/GSSG)], the mitochondrial morphology, and the proteins and membrane potential were determined. Our results showed that the neuronal mitochondria functionality was altered after being cocultured with senescent astrocytes. In vivo, we found that old animals had diminished mitochondrial oxidative phosphorylation (OXPHOS) proteins, redox state, and senescence markers as compared to young rats, suggesting effects of the senescent astrocytes similar to the ones we observed in vitro. Overall, these results indicate that the microenvironment generated by senescent astrocytes can affect neuronal mitochondria and physiology.